FL% is associated with the severity of acute DeBakey type I aortic dissection in patients undergoing frozen elephant trunk and total arch replacement - Wang, Long-Fei; Li, Yu; Jin, Mu; Li, Hai-Bin; Zhang, Nan; Gong, Ming; Zhang, Hong-Jia; Liu, Yu-Yong; Lai, Yong-Qiang (Frontiers in Surgery, 2024)
OBJECTIVES: The diameter, area, and volume of the true lumen and false lumen (FL) have been measured in previous studies to evaluate the extent of DeBakey type I aortic dissection. However, these indicators have limitations because of the irregular shapes of the true and false lumens and the constant oscillation of intimal flap during systole and diastole. The ratio of arch lengths seems to be a more reliable indicator. FL% was defined as the ratio of the arch length of FL to circumference of aorta in the different levels of aorta. The purpose of this article was to investigate whether FL% is a predictor of the severity of acute DeBakey type I aortic dissection in patients undergoing frozen elephant trunk (FET) and total arch replacement. METHODS: In this retrospective observational study, we analyzed a total of 344 patients with acute DeBakey type I aortic dissection who underwent FET and total arch replacement at our center from October 2015 to October 2019. Patients were divided into two groups by cluster analysis according to the perioperative course. Binary logistic regression analyses were performed to determine whether FL% could predict the severity of acute DeBakey type I aortic dissection. The area under the receiver operating characteristic curve (AUROC) was used to assess the power of the multivariate logistic regression model for the severity of acute DeBakey type I aortic dissection. RESULTS: The ascending aortic FL%, location of initial tear, the degree of left iliac artery involvement , and the degree of right coronary artery involvement on preoperative CTA were associated with the severity of acute DeBakey type I aortic dissection. The AUROC value of ascending aortic FL% was 0.841 for the severity of acute DeBakey type I aortic dissection in patients undergoing FET and total arch replacement. CONCLUSIONS: Ascending aortic FL% was validated as an essential radiologic index for assessing the severity of acute DeBakey type I aortic dissection in patients undergoing FET and total arch replacement. Higher values of ascending aortic FL% were more severe.